Detection of Streptococcus pneumoniae, Neisseria meningitidis and Haemophilus influenzae in Culture Negative Cerebrospinal Fluid Samples from Meningitis Patients Using a Multiplex Polymerase Chain Reaction in Nepal - Supriya Sharma; Jyoti Acharya; Dominique A. Caugant; Megha Raj Banjara; Prakash Ghimire; Anjana Singh (MDPI AG, 2021)
The rapid identification of bacteria causing meningitis is crucial as delays in the treatment increase mortality rate. Though considered as the gold standard for the laboratory diagnosis of bacterial meningitis, culture might give false negative results in a case of patients under antibiotics prior to lumbar puncture. This study aimed to detect Streptococcus pneumoniae, Neisseria meningitidis and Haemophilus influenzae by a multiplex polymerase chain reaction (PCR) in culture-negative cerebrospinal fluid samples collected from clinically suspected meningitis cases attending different hospitals in Kathmandu, Nepal from January 2017 to December 2019. S. pneumoniae, N. meningitidis and H. influenzae were detected in 8.59% (33/384) of the specimens by PCR and 7.55% (29/384) of the specimens by culture. Correlation between culture and PCR of the same sample was good (Spearman's rho correlation coefficient = 0.932). However, the difference in positivity between culture and PCR was statistically not significant (p value > 0.05). In four specimens, culture could not detect any of the targeted bacteria whereas PCR could detect presence of H. influenzae. PCR increases the diagnostic yield for bacterial meningitis. PCR may be considered as an adjunctive test for establishing the cause of infection in culture negative clinically suspected meningitis cases.